2023
DOI: 10.1186/s12943-023-01839-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of radiotherapy resistance and radiosensitization strategies for esophageal squamous cell carcinoma

Lingbo An,
Mingyang Li,
Qingge Jia

Abstract: Esophageal squamous cell carcinoma (ESCC) is the sixth most common cause of cancer-related mortality worldwide, with more than half of them occurred in China. Radiotherapy (RT) has been widely used for treating ESCC. However, radiation-induced DNA damage response (DDR) can promote the release of cytokines and chemokines, and triggers inflammatory reactions and changes in the tumor microenvironment (TME), thereby inhibiting the immune function and causing the invasion and metastasis of ESCC. Radioresistance is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 197 publications
(218 reference statements)
0
14
0
Order By: Relevance
“…The abscopal effect relies on the presence of T cells, and radiotherapy may induce T cell depletion by increasing PD-L1 expression through the cGAS-Sting pathway, contributing to immune escape, reducing the abscopal effect, and increasing resistance to radiotherapy ( 19 , 20 ). Blocking the PD-L1 receptor can reverse T cell depletion, maintaining T cell immune homeostasis, which, in turn, enhances the abscopal effect during radiotherapy and overcomes radiotherapy resistance ( 21 , 22 ). Furthermore, tumor resistance to radiotherapy is often linked to tumor hypoxia caused by vascular abnormalities or dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The abscopal effect relies on the presence of T cells, and radiotherapy may induce T cell depletion by increasing PD-L1 expression through the cGAS-Sting pathway, contributing to immune escape, reducing the abscopal effect, and increasing resistance to radiotherapy ( 19 , 20 ). Blocking the PD-L1 receptor can reverse T cell depletion, maintaining T cell immune homeostasis, which, in turn, enhances the abscopal effect during radiotherapy and overcomes radiotherapy resistance ( 21 , 22 ). Furthermore, tumor resistance to radiotherapy is often linked to tumor hypoxia caused by vascular abnormalities or dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we reviewed the roles of NEDD4 and NEDD4L in various digestive diseases for the purpose of providing new strategies for the prevention and treatment of digestive diseases. Esophageal cancer is the seventh most common cancer worldwide and the sixth most common cause of cancer-related deaths [75,76]. Esophageal squamous cell carcinoma (ESCC) is a common subtype of esophageal cancer with a high incidence [77,78].…”
Section: The Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
“…The PI3K/Akt pathway can be irregularly activated via several mechanisms, including various genomic alterations such as mutations in PTEN, Akt, and mTOR mechanism[ 7 , 71 , 96 , 97 ]. Dysregulation of the RTK signaling pathway is implicated in the malignant progression of ESCC, including metastasis[ 4 , 98 , 99 ].…”
Section: The Genetic Mechanism Of Mirnas On Escc Metastasismentioning
confidence: 99%
“…This signaling pathway consists of several components, including Wnts, receptors (such as Frizzled, FZD and low-density lipoprotein receptor-related proteins, LRP), Dishevelled (Dsh/Dvl), β-catenin, glycogen synthase kinase 3β (GSK-3β), Axin, and APC (adenomatous polyposis coli). Research has shown that the Wnt/β-catenin signaling pathway is intricately linked with tumor development, partly as a significant contributor to the onset and metastasis of ESCC, including metastasis[ 98 , 110 ].…”
Section: The Genetic Mechanism Of Mirnas On Escc Metastasismentioning
confidence: 99%